2017
DOI: 10.3390/s17061340
|View full text |Cite
|
Sign up to set email alerts
|

Doppler Navigation System with a Non-Stabilized Antenna as a Sea-Surface Wind Sensor

Abstract: We propose a concept of the utilization of an aircraft Doppler Navigation System (DNS) as a sea-surface wind sensor complementary to its normal functionality. The DNS with an antenna, which is non-stabilized physically to the local horizontal with x-configured beams, is considered. We consider the wind measurements by the DNS configured in the multi-beam scatterometer mode for a rectilinear flight scenario. The system feasibility and the efficiency of the proposed wind algorithm retrieval are supported by comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…As the system of Equation (2) provides the up-wind direction retrieval, it is converted to the measured wind direction ψ w using the following equation [ 40 ]: …”
Section: Methodsmentioning
confidence: 99%
“…As the system of Equation (2) provides the up-wind direction retrieval, it is converted to the measured wind direction ψ w using the following equation [ 40 ]: …”
Section: Methodsmentioning
confidence: 99%
“…We have considered the airborne weather radar, FM-CW millimeter wave demonstrator system, and airborne Doppler navigation system equipped with a fixed-beam antenna performing measurements at the circular ground track [23,[25][26][27]. Also, we have studied the wind measurements by the airborne weather radar in the scanning-beam case, and by the airborne Doppler navigation system and multi-beam scatterometer in the multi-beam case at the rectilinear ground track [24,[28][29][30]. The research has shown that, in the general case, the wind speed and direction can be found using the system of N equations composed for the appropriate NRCSs obtained at the same incidence angle for each azimuth sector observed with the given azimuth step [30]:…”
Section: Methodsmentioning
confidence: 99%
“…As the azimuth angle α is counted from the up-wind direction, the measured (navigational) sea wind direction ψ w defines as [29]:…”
Section: Methodsmentioning
confidence: 99%
“…Recently in [37], we have demonstrated that in order to provide an accurate and unambiguous retrieval of the wind vector, at least four azimuthally star-configured beams (looks) are required at the same incidence angle. The airborne star geometry [38] and some other earlier considered airborne one- [39] or multi-beam [40][41][42][43] geometries or sector scanning airborne instruments operated in the scatterometer mode [44][45][46][47][48][49] cannot be implemented for the satellite scatterometer to observe the same cell and to achieve better sea ice and water discrimination. Therefore, using the azimuthal isotropy of the sea ice backscattering in contrast to the anisotropy of the water surface backscattering, we considered another five hypothetical, fixed fan-beam scatterometer geometry constructed by adding an "extra" fore-antenna and an "extra" aft-antenna having 32.5 • and 147.5 • azimuthal directions relative to the spacecraft ground track, respectively, [25] as presented in Figure 3.…”
Section: Methodsmentioning
confidence: 99%